A Decrease to Low Carbonate Clumped Isotope Temperatures in Cryogenian Strata. Issue 3 (11th September 2020) - Mackey, T. J.; Jost, A. B.; Creveling, J. R.; Bergmann, K. D.
Abstract: Preglacial and synglacial low‐latitude carbonate sediments of the Elbobreen Formation, NE Svalbard, preserve facies changes associated with low‐latitude glacial advance in Cryogenian "Snowball Earth" episodes (717–635 Ma). We present the first application of carbonate clumped (Δ47 ) isotope thermometry on synglacial Snowball Earth carbonates and combine results with sedimentologic and petrographic observations and stable isotope ( δ 13 C and δ 18 O) geochemistry to assess Neoproterozoic environmental change. We find elevated calcite Δ47 temperatures, which likely reflect solid‐state reordering during burial. Dolomites, however, record lower temperatures that vary with facies and stratigraphy. Preglacial dolomite Δ47 temperatures range from 48–77°C, with a reconstructed fluid δ 18 OVSMOW value of +0.6‰ in the coldest sample. Glacial diamictites and dolomicrites comprise (1) reworked detrital clasts similar to preglacial strata in stable isotope composition and petrographic textures and (2) autochthonous dolomicrite with more positive δ 18 O values than those of preglacial dolomites or cooccurring detrital clasts. Mean glacial autochthonous dolomicrite Δ47 temperatures are 26 ± 10°C (95% CL) cooler than preglacial strata, with four samples <25°C. All dolomite Δ47 temperatures reflect diagenesis associated with lithification, yet observed stratigraphic and textural Δ47 temperature differences indicate that this occurred early and only contributes to part of the preserved temperature signal. Alteration trends within populations are consistent with low water/rock ratio diagenesis or partial solid‐state reordering; either possibility supports the likelihood of preserved δ 18 O trends. We postulate that the preserved temperature and δ 18 O differences between low‐latitude preglacial Tonian and synglacial Cryogenian dolomites are an imperfect reflection of primary temperature change and ice sheet expansion. Plain Language Summary: Glaciations, termed "Snowball Earth" episodes, with evidence for low‐latitude ice took place in the Cryogenian (717–635 Ma), and these extreme glaciations were likely a critical part of the transition between the Precambrian and the Phanerozoic (541 Ma to present). In this study, we analyzed strata from Svalbard that were originally deposited near the equator before and during one of these Snowball Earth events and present the first application of carbonate clumped isotope (Δ47 ) thermometry to Cryogenian synglacial deposits. We combine Δ47 results with both 18 O/ 16 O stable isotope composition of the carbonates and their microscopic character to assess evidence for environmental changes associated with this glaciation. Carbonates maintain a record of significantly (20–30°C) lower Δ47 temperatures in glacial versus preglacial deposits. Carbonate 18 O/ 16 O enrichment in synglacial deposits is consistent with ice sheet expansion in the Cryogenian. If the observed drop in temperature from preglacial to glacial strata reflects a difference in primary or shallow pore fluid temperatures, it far exceeds that of more recent Phanerozoic glaciations like the Pleistocene. Key Points: Neoproterozoic preglacial and glacial carbonates preserve differences in δ 18 O and carbonate clumped isotope temperatures A population of synglacial dolostones yield mean Δ47 temperatures 26 ± 10 °C (95% CL) cooler than lithified preglacial dolostones Clumped isotope temperatures <25°C ( n = 4) bolster confidence in a depositional or early diagenetic source for the δ 18 O isotopic record